(untitled) (Международный научный журнал «Инженер», 2026)
The article presents the results of research on the surface-active properties of local mineral fillers using the method of determining the distribution of adsorption centers (DAC). Based on the obtained results for determining the surface-active properties of local mineral fillers, a unified criterion for scientifically grounded prediction of the behavior of mineral fillers in the composition of asphalt concrete is proposed. The proposed criterion for assessing the acid-base properties of the surface of mineral fillers, using the indicator of "normalized chemisorption activity," shows a high convergence of the results with the outcomes of previously conducted studies and can be adopted as the basis for predicting and regulating the physical-mechanical and operational properties of asphalt concrete.